2011
DOI: 10.4062/biomolther.2011.19.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyoxyethylene Alkyl Esters on Permeation Enhancement and Impedance of Skin

Abstract: 2001). Lipid barrier of the skin was largely impaired after Isopropyl mirystate treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It was confirmed that small E chain could contribute to the enhancement effect of the surfactant, according to literature data (24) but the dependence of the enhancement effect on the lipophylic portion was not so marked. Two different patterns were found considering the E chain equal to 8 or 12 and mono-or di-derivatives; the PEG8 monoderivatives permitted to obtain higher ER values than PEG12, while for dioleate trend resulted opposite (Table I).…”
Section: Discussionsupporting
confidence: 68%
“…It was confirmed that small E chain could contribute to the enhancement effect of the surfactant, according to literature data (24) but the dependence of the enhancement effect on the lipophylic portion was not so marked. Two different patterns were found considering the E chain equal to 8 or 12 and mono-or di-derivatives; the PEG8 monoderivatives permitted to obtain higher ER values than PEG12, while for dioleate trend resulted opposite (Table I).…”
Section: Discussionsupporting
confidence: 68%